The Development of Web-Based Paperless Office System Using CodeIgniter Framework Case Study of Lembaga Pengembangan Cabang Ranting Muhammadiyah - Bagus, Yerezqy; Rahman, Arif; Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2020)
Lembaga Pengembangan Cabang Ranting (LPCR) Muhammadiyah Yogyakarta is an institution that often conducts correspondence between institutions. The activity of recording incoming and outgoing mail data at LPCR Yogyakarta still uses the manual method by recording in a ledger. In addition, the length of time required in the letter of submission is also still found in the LPCR. One method that can be used to overcome this is paperless office, where the work environment that uses paper is eliminated or greatly reduced. The use of paperless office in addition to saving paper can also improve the efficiency of data processing and search because the form is already digital. This system was built using the Unified Software Development Process (USDP) development method, with the Unified Modeling Language (UML) modeling. In the initial process, the initial phase is an analysis of requirements for software requirements. Furthermore, at the elaboration stage, the maturation of concepts that have been analyzed in the previous phase is carried out. Then at the development stage, system development is done with the PHP programming language and MySQL database using the CodeIgniter framework. The final phase is the transition carried out alpha testing and beta testing. The alpha test results of the system built went well, while for the beta test results at the Administrator level, the results were 86.8% Strongly Agree and 13.2 Strongly Disagree, 86.4% Strongly Agree and 13.6% Strongly Disagree of Headoffice users, 91.3% Strongly Agree and 8.7% Strongly Disagree from the results of the operators' user answers and 96% Strongly Agree and 4% Strongly Disagree from the results of the Guest user. Based on the test results, the system built is feasible and can be used by LPCR Yogyakarta.